INDUKSI KALUS KENTANG ASAL DESA DOMBU (SOLANUM TUBEROSUM L.) DENGAN ZPT INDOLE-3-ACETIC ACID (IAA) - Zulraufianti, Lyly; Paserang, Asri Pirade (Univ. Tadulako, 2019)
The research of callus induction in potato (S. tuberosum L.) from Dombu Village with indole-3-acetic-acid (IAA) was conducted from Januari to April 2019 in Laboratory of Tissue Culture, Biology Department, Faculty of Mathematics and Natural Science, Tadulako University. The research was aimed to determine of concentration IAA of the best to induce callus. This study was designed based on Completely Randomized Design (CRD) with 5 treatments, 3 replications and 3 explants on each unit. The treatments were P1= MS + 0 ppm, P2= MS + 0.5 ppm, P3= MS + 1.0 ppm, P4= MS + 2.0 ppm, P5= MS + 3.0 ppm. The results showed that the best and the efficient treatments for induction of callus treatment was P4= MS + 2.0 ppm with to induce callus up to 100%, the callus colour was yellow to brown and intermediate texture.